Targeting NR4A Nuclear Receptors to Control Stromal Cell Inflammation, Metabolism, Angiogenesis, and Tumorigenesis - Crean, Daniel; Murphy, Evelyn P. (Frontiers in Cell and Developmental Biology, 2021)
The NR4A1-3 subfamily of nuclear receptors are immediate early genes induced by a pleiotropy of stimuli including peptide hormones, growth factors, cytokines, inflammatory and physiological stimuli and cellular stress. NR4A receptors function as potent sensors of changes in the cellular microenvironment to control physiological and pathological processes through genomic and non-genomic actions. NR4A receptors control metabolism, cardiovascular and neurological functions and mediate immune cell homeostasis in inflammation and cancer. This receptor subfamily is increasingly recognized as an important molecular connection between chronic inflammation, altered immune cell responses and cancer development. In this review we examine how transcriptome analysis identified NR4A1/2 receptors as transcriptional regulators in mesenchymal stromal cell (MSC) migration, cell cycle progression and cytokine production to control local immune responses. In chronic inflammatory conditions, such as rheumatoid arthritis, NR4A receptors have been shown to modify the activity of MSC and fibroblast-like stromal cells to regulate synovial tissue hyperplasia, pathological angiogenesis and cartilage turn-over in vivo. Additionally, as NR4A1 has been observed as a major transcriptional regulator in tumour-stromal communication controlling tumorigenesis, we discuss how advances in the pharmacological control of these receptors is leading to important new mechanistic insights into understanding the role of stromal cells in health and disease.